Gamma-irradiated rotavirus: A possible whole virus inactivated vaccine. - Shabihah Shahrudin; Cheng Chen; Shannon C David; Eve V Singleton; Justin Davies; Carl D Kirkwood; Timothy R Hirst; Michael Beard; Mohammed Alsharifi (PLoS ONE, 2018)
Rotavirus (RV) causes significant morbidity and mortality in developing countries, where children and infants are highly susceptible to severe disease symptoms. While live attenuated vaccines are available, reduced vaccine efficacy in developing countries illustrates the need for highly immunogenic alternative vaccines. Here, we studied the possible inactivation of RV using gamma(γ)-irradiation, and assessed the sterility and immunogenicity of γ-irradiated RV (γ-RV) as a novel vaccine candidate. Interestingly, the inactivation curve of RV did not show a log-linear regression following exposure to increased doses of γ-rays, and consequently the radiation dose required to achieve the internationally accepted Sterility Assurance Level could not be calculated. Nonetheless, we performed sterility testing based on serial passages of γ-RV, and our data clearly illustrate the lack of infectivity of γ-RV preparations irradiated with 50 kGy. In addition, we tested the immunogenicity of 50 kGy γ-RV in mice and our data illustrate the induction of strong RV-specific neutralising antibody responses following administration of γ-RV without using adjuvant. Therefore, whilst γ-RV may not constitute a replacement for current RV vaccines, this study represents a proof-of-concept that γ-irradiation can be applied to inactivate RV for vaccine purposes. Further investigation will be required to address whether γ-irradiation can be applied to improve safety and efficacy of existing live attenuated vaccines.